1985
DOI: 10.1149/1.2113935
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of ZrC — Equilibrium Condition Calculated for Deposition from a  CH 4 ‐ ZrCl4 ‐  H 2 Gaseous Mixture

Abstract: Chemical vapor deposition of the nonstoichiometric zirconium carbide is computed by minimization of the Gibbs free energy of the system. Analytical expressions for the Gibbs free energy of formation of ZrxC1−x f.c.c. solid and liquid phases are set up, and the deposition diagram with “isostoichiometric curves” is presented as a function of ZrCl4 , CH4 , and H2 pressures in the input gas mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Several studies reported the CVD of zirconium carbide and carbon-zirconium carbide alloys [10][11][12][13][14][15][16][17][18]. The ZrC coatings are generally synthesized by zirconium halide [11,12] and hydrocarbons, such as CH 4 and C 3 H 6 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the CVD of zirconium carbide and carbon-zirconium carbide alloys [10][11][12][13][14][15][16][17][18]. The ZrC coatings are generally synthesized by zirconium halide [11,12] and hydrocarbons, such as CH 4 and C 3 H 6 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The carbon sources are CH 4 or a high‐carbon‐content hydrocarbon 8 . The process parameters have also been intensively studied, including the thermodynamics, carbon source effect, zirconium source effect, and hydrogen effect 6,8,11–13 …”
Section: Introductionmentioning
confidence: 99%
“…12,15,17 Thermodynamic studies of the ZrC deposition process have also been carried out in previous studies. 13,18,19 To better control the ZrC deposition process, it is necessary to understand the deposition mechanism. However, the study has seldom been done to elucidate such a mechanism.…”
Section: Introductionmentioning
confidence: 99%